2016
DOI: 10.1016/j.pacs.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Multiple irradiation sensing of the optical effective attenuation coefficient for spectral correction in handheld OA imaging

Abstract: Spectral optoacoustic (OA) imaging enables spatially-resolved measurement of blood oxygenation levels, based on the distinct optical absorption spectra of oxygenated and de-oxygenated blood. Wavelength-dependent optical attenuation in the bulk tissue, however, distorts the acquired OA spectrum and thus makes quantitative oxygenation measurements challenging. We demonstrate a correction for this spectral distortion without requiring a priori knowledge of the tissue optical properties, using the concept of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…When the sphere was uniformly illuminated, its entire surface became visible with the reconstructed images, accurately resembling the theoretically predicted (simulated) values. Even though it has been shown that OA images can, in principle, be corrected for nonuniform illumination and light attenuation, it was not necessary in this case . Such correction for limited‐view conditions or for a relatively low number of measuring positions can be still hampered by streak‐type artifacts associated with strong nonuniformity of the excitation light field (hot spots) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the sphere was uniformly illuminated, its entire surface became visible with the reconstructed images, accurately resembling the theoretically predicted (simulated) values. Even though it has been shown that OA images can, in principle, be corrected for nonuniform illumination and light attenuation, it was not necessary in this case . Such correction for limited‐view conditions or for a relatively low number of measuring positions can be still hampered by streak‐type artifacts associated with strong nonuniformity of the excitation light field (hot spots) .…”
Section: Discussionmentioning
confidence: 99%
“…To this end, several experimental and algorithmic strategies have been attempted in order to mitigate image artifacts related to suboptimal object illumination . Here, we introduce an optimized design for light delivery in three‐dimensional OA tomography based on the combination of a custom‐made optical fiber bundle with a 3D‐printed (fused deposition modeling (FDM)) sample chamber providing homogenous sample illumination.…”
Section: Introductionmentioning
confidence: 99%
“…First, the PA signal amplitude is proportional not only to absorption, but also to laser fluence (i.e., light level at a target) [7,8]. Because tissue attenuation depends on wavelength [33], the absorption spectrum estimated from a PA image can be very inaccurate (i.e., the shape can change dramatically and the wavelength of maximum absorption shift), especially deep within tissue [34,35]. This is illustrated in Figs.1a,c and clearly demonstrated in Results.…”
Section: Mainmentioning
confidence: 99%
“…Unfortunately, this requires a precise map of tissue optical properties, which cannot be measured or calculated during imaging. Several methods have attempted to estimate and compensate fluence variations [34][35][36][37][38][39][40][41][42][43], but none work well clinically where real-time or near real-time corrections are needed. In most cases, fluence is compensated using an approximate exponential function equalizing intensities.…”
Section: Mainmentioning
confidence: 99%
“…To evaluate the accuracy of the fluence distributions determined with NIROT/NIRFAST used to perform the correction, they were compared to reference fluence distributions. In phantom 1, the light fluence can be calculated by the light diffusion approximation Φ D ( r ) for a semi‐infinite, homogeneous medium : ΦD()rzd3()1d·3μaμs1/2ed·3μaμs1/2, where d is the distance between the OA illumination point on the phantom's surface and the position r . Phantom 1 served as a reference to (1) demonstrate the performance attainable with NIROT/NIRFAST, as the reconstructions for such a volume are expected to yield reliable results without any a priori knowledge, and to (2) experimentally establish the efficiency of quantitative OA imaging with our system.…”
Section: Experimental Tissue Modelmentioning
confidence: 99%